2021
DOI: 10.1097/sap.0000000000002682
|View full text |Cite
|
Sign up to set email alerts
|

Prepectoral Versus Subpectoral Breast Reconstruction in High–Body Mass Index Patients

Abstract: Background The effect of body mass index (BMI) on complication rates in prepectoral implant-based breast reconstruction is not well established. The purpose of this study was to compare complication rates between different BMI groups in subpectoral and prepectoral reconstruction. Methods A single-surgeon, 4-year, retrospective review was performed of consecutive prosthetic breast reconstructions. During this time, the senior author's practice shifted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…This year, the OPBC voting results stressed the need for phase III RCTs to specifically address the optimal timing of implant-based BR, the positioning of implants and the use of adjunctive mesh. Of note, multiple observational studies over the past three years on pre-versus sub-pectoral implant-based BR have predominantly shown either no difference or marginally favoured pre-pectoral positioning [ [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] ]. However, most were small, retrospective and single-centre studies, with only a few prospective or multicentre studies [ 25 , 26 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…This year, the OPBC voting results stressed the need for phase III RCTs to specifically address the optimal timing of implant-based BR, the positioning of implants and the use of adjunctive mesh. Of note, multiple observational studies over the past three years on pre-versus sub-pectoral implant-based BR have predominantly shown either no difference or marginally favoured pre-pectoral positioning [ [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] ]. However, most were small, retrospective and single-centre studies, with only a few prospective or multicentre studies [ 25 , 26 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, 15 studies were included in this meta-analysis. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]…”
Section: Study Screeningmentioning
confidence: 99%
“…All 15 studies that reported clinical outcomes were observational studies. Eight studies were from the United States 15,16,20,22,23,[25][26][27] ; four studies from Italy 17,24,28,29 ; one study from Korea 18 ; one study from United Kingdom 19 ; and one study from Germany. 21 The sample size ranged from 63 to 642 patients.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations